Phenotypic characterization of two novel cell line models of castration‐resistant prostate cancer. Issue 15 (16th August 2021) - Haffner, Michael C.; Bhamidipati, Akshay; Tsai, Harrison K.; Esopi, David M.; Vaghasia, Ajay M.; Low, Jin‐Yih; Patel, Radhika A.; Guner, Gunes; Pham, Minh‐Tam; Castagna, Nicole; Hicks, Jessica; Wyhs, Nicolas; et al.
Abstract: Background: Resistance to androgen deprivation therapies is a major driver of mortality in advanced prostate cancer. Therefore, there is a need to develop new preclinical models that allow the investigation of resistance mechanisms and the assessment of drugs for the treatment of castration‐resistant prostate cancer. Methods: We generated two novel cell line models (LAPC4‐CR and VCaP‐CR) which were derived by passaging LAPC4 and VCaP cells in vivo and in vitro under castrate conditions. We performed detailed transcriptomic (RNA‐seq) and proteomic analyses (SWATH‐MS) to delineate expression differences between castration‐sensitive and castration‐resistant cell lines. Furthermore, we characterized the in vivo and in vitro growth characteristics of these novel cell line models. Results: The two cell line derivatives LAPC4‐CR and VCaP‐CR showed castration‐resistant growth in vitro and in vivo which was only minimally inhibited by AR antagonists, enzalutamide, and bicalutamide. High‐dose androgen treatment resulted in significant growth arrest of VCaP‐CR but not in LAPC4‐CR cells. Both cell lines maintained AR expression, but exhibited distinct expression changes on the mRNA and protein level. Integrated analyses including data from LNCaP and the previously described castration‐resistant LNCaP‐abl cells revealed an expression signature of castration resistance. Conclusions: The two novel cell line models LAPC4‐CR and VCaP‐CR and their comprehensive characterization on the RNA and protein level represent important resources to study the molecular mechanisms of castration resistance.